SISTEM INFORMASI PERUMAHAN PURIMAS CITRA GEMILANG 2 BERBASIS MOBILE - Arya Gemilang Deva Purwanto; Zainudin Zukhri (STKIP PGRI Situbondo, 2023)
The development of information technology is increasing rapidly. Such developments affect the speed of obtaining information. Unfortunately, there are still many needs for good and comfortable housing that has not used a good information system to facilitate housing management and data collection such as in Purimas Citra Gemilang 2 Housing, a housing that has facilities to meet the needs of its residents. In managing housing, there are often obstacles in terms of data collection management such as monthly contribution payments, registration of prospective new residents, and recording of housing residents. This is because the recording is still manual. The use of technology, especially mobile-based applications, can optimize housing implementation by providing an integrated data management system that can be accessed via smartphones. Modern housing needs an application that can support the population system. On that basis, it is hoped that the application